Accurate: Penunjang di Era Digitalisasi untuk Meningkatkan Kompetensi dan Profesionalisme Guru dan Murid SMK - Debora; Alexander , Nico; K. P. S. Putri, Ariesta Tika; A. T. Lasar, Hilary Flora (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2022)
Abstract - Covid-19 pandemic has brought many changes for education, working life and so on. Digitalization is increasingly felt and forced to change from being face-to-face to online, so inevitably world moves faster to accelerate the use of technology. Technology development also applied in industry, including in terms of accounting records. The importance of debriefing for teachers and students of VHS, especially accounting vocational, related to using Accurate accounting software which has been widely used. This training improves self-competence and competitiveness in the face of digitalization. Therefore, Pusat Penelitian dan Pengabdian Masyarakat TSM in collaboration with TSM lecturers help to provide training for teachers and students to recognize and able to operate one of accounting software that has been widely used, especially by SME industry in Indonesia, namely Accurate. The purpose of this training is to provide briefing to teachers and students in understanding and operating various features in Accurate related to accounting transactions which are expected to improve skills in using this software. The training method includes Accurate introduction session, simulation, journal and financial statements discussion. Targets and outcomes to be achieved from this training are increased the understanding and skills of teachers and students in operating Accurate so the students could meet the requirements of world of work in terms of the use of technology.